Susceptibility Profile and Epidemiological Cut-Off Values Are Influenced by Serotype in Fish Pathogenic Streptococcus agalactiae - Carlos Augusto Gomes Leal; Brendhal Almeida Silva; Salene Angelini Colombo (MDPI AG, 2023)
Streptococcus agalactiae is a major health concern in tilapia farming worldwide. In contrast to the availability of susceptibility profile results, interpretative criteria for disk diffusion assays and the influence of serotypes on resistance profiles are not available. To address this, sixty isolates (thirty of each serotype, Ib and III) were evaluated using the disk diffusion assay against six antibiotics, and the epidemiological cut-off value (ECV) was calculated. All the isolates were classified as non-wild type (NWT) for sulfamethoxazole (SUT) and norfloxacin (NOR). The inhibition zones for oxytetracycline (OXY) and doxycycline (DOX) were largely distinct; all serotype Ib and III isolates were classified as wild-type (WT) and NWT, respectively. The results for serotype III of fish group B Streptococcus (GBS) were comparable to the NWT tetracycline profile of human GBS available in EUCAST, suggesting the presence of resistance mechanisms in these fish isolates. The calculation of the cut-off wild type (COWT) values for OXY and DOX was appropriate for both serotypes. Differences between the distribution of florfenicol (FLO) and amoxicillin (AMO) were found, and we attribute this to the faster growth rate of serotype III, which promotes smaller inhibition zones. Therefore, using separate COWT for each serotype is necessary. In conclusion, the serotype of fish GBS affects its susceptibility profile, and it is recommended to use serotype-specific COWT values as interpretative criteria for disk diffusion assays against FLO and AMO.